The World Health Organization’s changing goals and expectations concerning malaria, 1948-2019 - Socrates Litsios (História, Ciências, Saúde: Manguinhos, 2020)
Abstract From its inception, in 1948, the World Health Organization made control of malaria a high priority. Early successes led many to believe that eradication was possible, although there were serious doubts concerning the continent of Africa. As evidence mounted that eradicating malaria was not a simple matter, the malaria eradication programme was downgraded to a unit in 1980. Revived interest in malaria followed the Roll Back Malaria Initiative adopted in 1998. This article presents an historical account of the globally changing ideas on control and elimination of the disease and argues that insufficient attention was paid to strengthening health services and specialized human resources.